2020
DOI: 10.1186/s12879-020-05103-6
|View full text |Cite
|
Sign up to set email alerts
|

Clients’ perceptions of barriers and facilitators to implementing hepatitis C virus care in homeless shelters

Abstract: Background: Hepatitis C virus (HCV) is highly prevalent among homeless persons, yet barriers continue to impede HCV testing and treatment in this population. We studied the experiences of homeless individuals related to accessing HCV care to inform the design of a shelter-based HCV prevention and treatment program. Methods: Homeless shelter clients (10 women and 10 men) of a large shelter in San Francisco participated in gender segregated focus groups. Focus groups followed a semi-structured interview format, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 32 publications
0
62
0
Order By: Relevance
“…This study employed multiple resources in an effort to engage patients including centralized identification of viremic patients, staged outreach and group classes where patients could also undergo labs and imaging. Importantly, patients were informed of curative medications, a knowledge barrier that keeps homeless persons from seeking treatment 7 . In logistic regression, they identified homelessness to be a statistically independent factor associated with non‐engagement in HCV care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study employed multiple resources in an effort to engage patients including centralized identification of viremic patients, staged outreach and group classes where patients could also undergo labs and imaging. Importantly, patients were informed of curative medications, a knowledge barrier that keeps homeless persons from seeking treatment 7 . In logistic regression, they identified homelessness to be a statistically independent factor associated with non‐engagement in HCV care.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the high prevalence rate, persons experiencing homelessness encounter many barriers to treatment. Masson et al 7 stratified these barriers into individual, system, and social‐level barriers. Identified barriers on the individual level included comorbid medical and psychiatric conditions as well as misconceptions about HCV.…”
Section: Introductionmentioning
confidence: 99%
“…1 While direct-acting antiviral (DAA) therapy is highly effective for HCV treatment, there are barriers to DAA treatment uptake among persons experiencing homelessness related to access to medication, substance use problems and difficulty with engaging in on-going care, among others. 2 Patient-reported experiences (PREs) measure patients' perspectives of their general health, quality of life and psychosocial experiences relating to their disease and its management. 3 These factors are critical in addressing patient concerns during HCV therapy and scaling DAA therapy in hard to engage populations.…”
Section: Introductionmentioning
confidence: 99%
“…4 In this study, we aimed to assess PREs in patients experiencing homelessness during HCV daa therapy in an integrated homeless shelter-based model of HCV care that was implemented following assessment of key stakeholders' perspectives. 2,5 1) associated with PREs were evaluated using univariable and multivariable logistic regression models. Statistical significance was defined at p-value of <.05 (two-sided).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have shown that despite near universal screening for HCV in a birth cohort receiving care within a safety net health system, less than a quarter of patients infected with HCV were started on HCV treatment. ( 1 ) Structured and multidisciplinary approaches to HCV care with input from key stakeholders, including patients, ( 2 ) are therefore required to meet the needs of the homeless populations infected with HCV. Based on these findings, we have successfully implemented an integrated model of on‐site shelter‐based HCV testing, education, and treatment to scale up HCV care in the homeless shelters across two urban and geographically diverse cities.…”
mentioning
confidence: 99%